Bradycardia-Induced Recurrent Torsade de Pointes: When Serenity Turns into Chaosity - Laksmi Senja Agusta; Harnanik P. Riswati; Rizal R. Akbar; Ardian Rizal (Publisher: Shahid Beheshti University of Medical Sciences, 2018)
Torsade De Pointes is typical form of polymorphic ventricular tachycardia. It was in the setting of bradycardia when first described. We present a case of patient coming to emergency room with torsade de pointes development who was found to have bradycardia on basal electrocardiography record. In fact, bradycardia has been shown as a cause of acquired long QT syndrome that can lead to torsade de pointes. The inverse relationship between heart rate and repolarization time primarily accounts for QT prolongation. Finally, proper treatment considering electrophysiology mechanism is essential to prevent mortality.